Kinesthesis Cues Aids Spatial Memory - Tan, Desney; Stefanucci, Jeanine K; Proffitt, Dennis R; Pausch, Randy ((2002) Extended Abstracts at CHI 2002 Conference on Human Factors in Computing Systems, 2002)
We are interested in building and evaluating human computer interfaces that make information more memorable. Psychology research informs us that humans access memories through cues, or “memory hooks,” acquired at the time we learn the information. In this paper, we show that kinesthetic cues, or the awareness of parts of our body’s position with respect to itself or to the environment, are useful for recalling the positions of objects in space. We report a user study demonstrating a 19% increase in spatial memory for information controlled with a touchscreen, which provides direct kinesthetic cues, as compared to a standard mouse interface. We also report results indicating that females may benefit more than males from using the touchscreen device.